Modification of Glassy Carbon Electrode by a Simple, Inexpensive and Fast Method Using an Ionic Liquid Based on Immidazolium as Working Electrode in Electrochemical Determination of Some Biological Compounds - MOJTABA MOSTAFAVI, S.; ROUHOLLAHI, AHMAD; ADIBI, MINA; MOHAJERI, ALI; PASHAEE, FARSHID; PYRIAEE, MASOUMEH (Asian Journal of Chemistry, 2011)
To achieve a simple, inexpensive and fast method for modification of glassy carbon electrode (GCE) by ionic liquids is the aim of this study. For this purpose, the surface of glassy carbon electrode was modified with 3-methyl-1-octylimidazolium hexaflourophosphate [omim][PF6] and determination of dopamine, ascorbic acid and uric acid was done simultaneously. In this method, modification of surface electrode was done by pouring the droplet of dissolved ionic liquid in acetonitrile on surface of glassy carbon electrode. After this stage, the surface was stabled by taking cyclic voltammetry and electrochemical properties of dopamine, ascorbic acid and uric acid were investigated by cyclic voltammetry on glassy carbon electrode modified with [omim][PF6] ionic liquids. Then, this species was measured by differential pulse voltammetry (DPV) in human serums. Under optimal conditions, the linear calibration curves in the ranges of 5 × 10-6 - 5 × 10-3 M, 1 × 10-5 - 5 × 10-3 M and 5 × 10-6 - 1 × 10-4 were obtained for dopamine, ascorbic acid and uric acid respectively. Detection limit of current of this technique was about 2 × 10-6, 5 × 10-6 and 2 × 10-6 M for dopamine, ascorbic acid and uric acid respectively. The relative standard deviation for 10 measurements of dopamine (1 × 10-4), ascorbic acid (5 × 10-4) and uric acid (5 × 10-4) were determined to be 3.21, 2.88 and 3.57 %, respectively. The simultaneous determination of these species in human serum was done successfully.